Factors Affecting Energy-Saving Intentions among Youth in Vietnam - Le Thi Dieu Hien; Huyen, Khuu Ngoc; Hoang, Thi Hong Loc (International Journal of Energy Economics and Policy, 2023)
This study aims to demonstrate the factors that influence the energy-saving intentions of youth in Vietnam. The study applies an expanded Theory of Planned Behavior (TPB) model with the addition of moral norms, product quality, and energy policy to enhance the explanatory power of youth’s energy-saving intentions. The research data were collected using a stratified random sampling method with a sample size of 263 respondents from 5 provinces/cities: Ho Chi Minh City, Can Tho City, Binh Thuan Province, Dong Thap Province, and Kien Giang Province. By employing Structural Equation Modeling (SEM) method, the study has demonstrated the positive factors influencing youth’s energy-saving intentions, including attitudes towards energy-saving, perceived behavioral control, subjective norms, personal ethical standards, product quality, and energy policies. Among these factors, attitudes towards energy saving have the most impact on the energy-saving intentions of youth.